Effect of Dextran infusion on the Adenosine Diphosphate Induced Adhesiveness and the Spreading Capacity of Human Blood Platelets - Bygdeman, S; Eliasson, R; Gullbring, B (Thrombosis and Haemostasis, 1966)
The adenosine diphosphate induced platelet adhesiveness to glass and the platelet spreading capacity on a siliconized glass surface have been studied in 8 hypovolemic subjects after infusion of 500 ml 6% solution of dextran 70 (Macrodex®) or 500 ml normal saline. Infusion of dextran caused a significant decrease in platelet adhesiveness compared with the controls while no effect was noted on the spreading capacity.It is proposed that the observed effect on platelet adhesiveness is due to dextran induced changes in the activity of plasma factors involved in the mechanisms leading to platelet adhesiveness.